1998
DOI: 10.1061/(asce)0899-1561(1998)10:2(66)
|View full text |Cite
|
Sign up to set email alerts
|

INNOVATIONS FORUM : Engineered Cementitious Composites for Structural Applications

Abstract: IntroductionIn the last several decades, concrete with increasingly high compressive strength have been used for structural applications. However, most of these materials remain brittle. In some cases, the brittleness as measured by the brittleness number (Hillerborg, 1983) actually increases as the compressive strength goes up. This poses potential danger and limitations of high strength concrete in structural applications. In certain locations, such as where steel and concrete come into contact (e.g. steel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(123 citation statements)
references
References 6 publications
0
121
0
2
Order By: Relevance
“…PVA-REC15 fibers were used at fixed volume fraction of 2% in the ECC specimens. Coarse aggregates are not used in preparing ECC [10,11]. Properties of fibers and mix properties of different concrete materials used in this study are presented in Tables 1 and 2 respectively.…”
Section: Test Programmentioning
confidence: 99%
See 1 more Smart Citation
“…PVA-REC15 fibers were used at fixed volume fraction of 2% in the ECC specimens. Coarse aggregates are not used in preparing ECC [10,11]. Properties of fibers and mix properties of different concrete materials used in this study are presented in Tables 1 and 2 respectively.…”
Section: Test Programmentioning
confidence: 99%
“…A number of recent studies have indicated that engineered cementitious composites (ECC), a unique type of highperformance fiber-reinforced cementitious composite, shows promise in overcoming the stress concentration problems [10]. ECC is a portland cement-based mortar matrix with a small volume fraction of polyvinyl alcohol (PVA) or polyethylene (PE) fibers (typically 2%).…”
Section: Type Of Concrete Materialsmentioning
confidence: 99%
“…Likewise, improvements in the mechanical performance of cement-based materials would also help to reduce their carbon footprint by enhancing their lifetime and durability. State-of-the-art methods to effectively reinforce concrete rely on precise micro-mechanical design in so-called Engineered Cementitious Composites (ECCs) [1,2]. Usually, ECCs are prepared with 10-30 mm long stainless steel fibers, with diameters from several hundreds of microns to a few millimeters.…”
Section: Introductionmentioning
confidence: 99%
“…UHTCC is often referred to as engineered cementitious composite (ECC) (Li and Kanda, 1998) or strain hardening cement-based composite (SHCC) (Boshoff and van Zijl, 2007). This type of material was developed to overcome the weaknesses of concrete, which include brittleness, low tensile deformability, low tensile strength, vulnerability to cracking, and the tendency of fine cracks to develop into wide cracks.…”
Section: Introductionmentioning
confidence: 99%